Cicatricial Tracheal Stenosis — A Long-Life Journey - A. A. Pechetov; G. A. Vishnevskaya; D. A. Volchanski; A. N. Lednev; I. I. Danilov; N. V. Gulova (Креативная хирургия и онкология)
Introduction. Since ancient times tracheostomy is known as a surgical procedure that ensures airway patency. According to current views, a non-idiopathic cicatricial tracheal stenosis develops within six weeks following the initiation of mechanical ventilation. When a patient presents with a characteristic history and complaints, the diagnosis of cicatricial tracheal stenosis poses no challenges.Aim. To present a series of observations of patients who underwent tracheostomy in childhood, whereas the cicatricial tracheal stenosis was diagnosed only in over 35 years after the onset of airway obstruction symptoms.Materials and methods. The study involved five patients (two men and three women) aged between 43 and 63 years. All patients had undergone tracheostomy in childhood, followed by subsequent decannulation. For over 35 years, the patients were monitored under the diagnosis of bronchial asthma. When a tracheal stenosis was identified, all patients underwent circular tracheal resection.Results and discussion. The duration of the surgical procedure ranged from 110 to 240 minutes. No complications that required re-surgery were recorded. All patients achieved healing of the tracheal anastomosis. The postoperative hospitalization period ranged from 10 to 15 days. The incidence of tracheal complications remains 0.2%–25%. The clinical onset of tracheal stenosis typically occurs within the first few months following decannulation. Functional diagnostic methods reveal a pattern of bronchial obstruction, which necessitates the administration of inhalation therapy using various groups of bronchodilator and anti-inflammatory medications. The most informative instrumental diagnostic techniques for tracheal diseases include laryngotracheoscopy and computed tomography.Conclusion. A history of tracheostomy or mechanical ventilation in patients presenting with complaints of dyspnea requires meticulous attention due to the risk of the development of cicatricial tracheal stenosis.